Bioreactor scale-up on rhamnolipid production by Pseudomonas aeruginosa RS6 based on constant impeller tip speed - Mahamad, Siti Syazwani; Mohamed, Mohd Shamzi; Radzuan, Mohd Nazren; Winterburn, James; Zakaria, Mohd Rafein (Springer Nature, 2025)
Rhamnolipids (RL) are glycolipid biosurfactants produced by microbes, commonly used in oil recovery and bioremediation. This study investigates the scale-up of RL production by Pseudomonas aeruginosa RS6 using biodiesel side stream waste glycerol as substrate, transitioning from a 1.5 to a 5 L bioreactor under a controlled constant impeller tip speed (Vtip) of 0.882 m s−1. Enhanced gas–liquid mass transfer was achieved in the 5 L system, reflected by a higher volumetric oxygen transfer coefficient () of 0.032 ± 0.00067 s−1 compared to 0.025 ± 0.00087 s−1 in the 1.5 L bioreactor. Correspondingly, the oxygen transfer rate (OTR) increased from 98.8 to 127.35 mmol L−1 h−1. Both RL yield and productivity increased by approximately 22% and 45%, reaching a final RL concentration of 16.48 ± 0.02 g L−1 and productivity of 0.22 ± 0.11 g L−1 h−1, respectively, in the 5 L bioreactor. Biomass of P. aeruginosa RS6 concentrations remained satisfactory across scales, indicating that shear forces did not compromise cell integrity. An opposite trend was observed in the oxygen uptake rate (OUR), suggesting prolonged oxygen availability and sustained microbial respiration in the 5 L bioreactor, likely driven by effective hydrodynamic control. Notably, produced RL maintained its high quality across both scales, exhibiting emulsification activity, EI24% of 62.38 ± 0.53 and 60.10 ± 0.34 on hydrophobic liquid kerosene and palm cooking oil, respectively. These findings validate constant Vtip as a robust scale-up strategy for RL production, effectively enhancing yield while maintaining microbial cell viability and physiological performance. By demonstrating consistent process behavior between bioreactor scales, this study provides experimental evidence that addresses common scale-up limitations, specifically poor scalability and reproducibility in RL biosurfactant production.